Design and Implementation of an IoT System for Indoor Measurement and Monitoring Fire and Gas Warning - Tri, Nguyen Van; Manh, Le Hung; Trung, Ha Duyen (Universitas Ahmad Dahlan, 2024)
Early detection and warning of fires occurring in homes is crucial to prevent loss of life and property. Fires can happen anywhere and at any time, but the presence of fire alarms helps keep homes safe. Therefore, early detection of fires will prove to be crucial as it could mean the difference between life and death. Most recently, the Internet of Things (IoT) technology has been deploying for data collection, transmission, storage and processing of large amounts of data from various sensor devices. Through the Internet, these sensors can be linked and help us manipulate or collect data from them. In this paper, we will use various types of sensors to sense the presence of fire and gas in the design and implementation of a completed IoT system. The designed IoT system aims to alert and assist homeowners, building guards, and firefighters about the presence of fire and gas leaks. Additionally, a common preventive solution is to install a sprinkler to spray water when the smoke sensor detects a fire. The designed system has been successfully implemented and tested in a variety of circumstances in an education bulding of University.